2015
DOI: 10.1021/acs.chemmater.5b03991
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Solution-Processed n-Doped Zirconium Oxide Cathode Buffer Layer for Efficient and Stable Organic and Hybrid Perovskite Solar Cells

Abstract: In this study, we present a simple and effective method to improve the performance and stability of organic and hybrid perovskite solar cells by the incorporation of solution-processed cetyltrimethylammonium bromide (CTAB)-doped zirconium oxide (ZrO x ) as cathode buffer layer (CBL). This novel n-doped ZrO x CBL possesses several remarkable features, including ease of fabrication without the need for thermal annealing or any other post-treatment, reasonable electrical conductivity (2.9 × 10–5 S cm–1), good am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 50 publications
1
28
0
1
Order By: Relevance
“…In this work the authors demonstrated how doping ZrO x with CTAB increases its electrical conductivity and improves device performance in comparison with devices applying the bare ZrO 2 oxide. Moreover, the ZrO x ‐based material can be fabricated at room temperature, and the final device shows high stability without the need for rigorous encapsulation . All these novel results suggest that there is still much room for improvement in the functionalization of oxide interfaces, semiconductors or inert scaffolds, for the enhancement of stability in PSCs.…”
Section: Functionalized Oxide Interfaces For Efficient Perovskite Solmentioning
confidence: 98%
See 1 more Smart Citation
“…In this work the authors demonstrated how doping ZrO x with CTAB increases its electrical conductivity and improves device performance in comparison with devices applying the bare ZrO 2 oxide. Moreover, the ZrO x ‐based material can be fabricated at room temperature, and the final device shows high stability without the need for rigorous encapsulation . All these novel results suggest that there is still much room for improvement in the functionalization of oxide interfaces, semiconductors or inert scaffolds, for the enhancement of stability in PSCs.…”
Section: Functionalized Oxide Interfaces For Efficient Perovskite Solmentioning
confidence: 98%
“…(n) ITO/NiCo 2 O 4 /perovskite/PC 61 BM:C 60 /ZrAcac/Ag . (o) ITO/PEDOT:PSS/perovskite/PC 61 BM/ZrO x /Ag and ITO/ PEDOT:PSS/perovskite/PC 61 BM/ZrO x ‐CTAB/Ag . (p) ITO/PEDOT:PSS/perovskite/PCBM/C 60 /Ag and ITO/CuNiO/perovskite/PCBM/C 60 /Ag .…”
Section: Introductionunclassified
“…PHJ p-i-n PSCs with a typical inverted structure (ITO/ PEDOT:PSS/perovskite/PCBM/metal) are promising for future flexible electronic devices due to their low-temperature processability [26]. It is important that the work functions of the cathode and anode match the quasi-Fermi levels of the active layers to ensure ohmic contact, maximum Voc, and minimal energy barrier for charge extraction to reduce interface carrier recombination [143,144]. Accordingly, low work function metals such as Al (~4.1 eV) or Ca (~2.9 eV) are sometimes used as cathode electrodes in PHJ p-i-n PSCs for efficient electron extraction (tables 1-4).…”
Section: Engineering the Interface Between The Electron Transporting mentioning
confidence: 99%
“…[9][10][11] The incomplete coverage of the interfacial layer can cause detrimental effects on devicep erformance and long-term stability. [17][18][19][20][21] Ar epresentative example is poly (3,4-ethylenedioxythiophene) (PEDOT) doped with poly(styrenes ulfonate) (PSS) anions (PEDOT:PSS), which representst he mostc ommonly used hole transportl ayer (HTL) in p-i-n typeP SCs (device configuration: substrate/anode/HTL/perovskite/electron transport layer (ETL)/ cathode)s of ar. [15,16] To overcomet hese intrinsic materials limitations, an effective approach is to incorporated opants into the host semiconductors (i.e.,d oping) to alter the carrier concentration and thus the electronic conductivity of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] To overcomet hese intrinsic materials limitations, an effective approach is to incorporated opants into the host semiconductors (i.e.,d oping) to alter the carrier concentration and thus the electronic conductivity of the materials. [17][18][19][20][21] Ar epresentative example is poly(3,4-ethylenedioxythiophene) (PEDOT) doped with poly(styrenes ulfonate) (PSS) anions (PEDOT:PSS), which representst he mostc ommonly used hole transportl ayer (HTL) in p-i-n typeP SCs (device configuration: substrate/anode/HTL/perovskite/electron transport layer (ETL)/ cathode)s of ar. [9,10] The PEDOT:PSS layer possesses several advantages as HTL such as favorable solution processability, high work function, and tunable conductivity.…”
Section: Introductionmentioning
confidence: 99%